2018
DOI: 10.3390/ijms19030848
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor, through Alleviating Oxidative Stress, Protect IPEC-J2 Cells from Lipopolysaccharides-Induced Apoptosis

Abstract: The epidermal growth factor (EGF) has been widely used for protection of stress-induced intestinal mucosa dysfunction. However, whether EGF would alleviate oxidative injury and reduce apoptosis in porcine intestine is not yet known. Therefore, the aim of this study was to investigate the effect of EGF on lipopolysaccharides (LPS)-induced induction of oxidative stress and ensuing apoptosis in the porcine intestinal epithelial cell line, IPEC-J2. The present study showed that EGF significantly increased cell via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 52 publications
7
59
1
2
Order By: Relevance
“…Various studies indicate the antitumor effects of H. pluvialis extract, which is rich in astaxanthin, being a potent growth inhibitor under laboratory conditions [16]. The results of the present study show anti-proliferative effects of astaxanthin seen by the increase in the expression of caspase 3, Bax, antioxidant activity conversely, decreasing the expression of bcl2, and the level of malondialdehyde in the LS-180 cell line [17,18]. A study reported that daily administration of astaxanthin could be effective in preventing colon cancer [19].…”
Section: Discussionsupporting
confidence: 63%
“…Various studies indicate the antitumor effects of H. pluvialis extract, which is rich in astaxanthin, being a potent growth inhibitor under laboratory conditions [16]. The results of the present study show anti-proliferative effects of astaxanthin seen by the increase in the expression of caspase 3, Bax, antioxidant activity conversely, decreasing the expression of bcl2, and the level of malondialdehyde in the LS-180 cell line [17,18]. A study reported that daily administration of astaxanthin could be effective in preventing colon cancer [19].…”
Section: Discussionsupporting
confidence: 63%
“…In previous studies, controversies still existed on whether LPS affect the viability and morphology of various cells. Different from Tang's results [12], in present study, the relative activity and morphology of cells exposed to 1, 5, and 10 µg/mL of LPS was not remarkably changed in comparison with the control group. However, Lee's results were similar to that of this research, where after continuous treatment with 1 µg/mL LPS for 24 h, the viability of HT29 and RAW264.7 cells showed no obvious changes, despite the different cell lines used [13].…”
Section: Discussioncontrasting
confidence: 99%
“…Once cells are exposed to oxidative stress, Nrf2 translocates into the nucleus and activates the transcription of genes containing ARE, such as heme oxygenase-1 (HO-1), glutathione S-transferase (GST) and thioredoxin reductase (TrxR). After being activated, the ARE-containing genes play their biologic role in antioxidant (Li et al, 2018b;Gan and Johnson, 2014;Tang et al, 2018). The significant effects of Nrf2 against oxidative stress-induced diseases have been verified.…”
Section: Discussionmentioning
confidence: 96%